KARYA SASTRA MUTAKHIR DENGAN KAJIAN PENDEKATAN GENDER - Setyawan - Pujiono (Universitas Negeri Yogyakarta, 2007)
Abstract Gender is a concept used to identify the differences between men and women. It has a strong relationship with literary work, that stories are employed by authors to communicate their messages and ideas from women. The results of the creativity are strongly influenced by the socio cultural condition of the authors. Female authors try to actively cooperate in responding the development of gender issues and using the chances to express their creative ideas into their literary works. Authors mean to change the gender issues perception through their literature works to make female equal to men in socio construction community. Female literary works are used as media in motivating women to do something to express their ideas so that women figures become a part of this real world who has the right to consider and admired. Recently, female literary works are almost equal to men’s in Indonesian literary world as a figure to show that women are not weak as what our community thought in patriarchy culture. Studies in female literary works such as Ayu Utami, Dewi Dee, and Djenar Maesa Ayu have given new colors in literary world. The colors are very useful agents of a change for women specially to life equal in the socio constructions community in the future.